Uji Organoleptik Hasil Jadi Kue Menggunakan Bahan Non Instant dan Instant - Dianka Wahyuningtias (Bina Nusantara University, 2010)
The process of making a cake in the modern era, demanding speed because of the time more valuable and more widely distribution coverage, which means greater production capacity. Then the process is made as efficient as possible. Busyness is high enough to make parents and family also eventually follow the diet and no hassle instant preparation. Now was enough just to buy one box of instant cake mix that is usually already included in the package, plus live eggs, and butter cake be desired. The process is also very clear instructions printed on the packaging of instant flour. From the results of analysis of Material Differences between Normal and Instant Ingredients (Paired Samples Correlations) then we can see the differences, views of significant value. If sig is smaller than 0:05, the materials A and B materials are different, but if the sig is greater than 0:05, the materials A and B, have same material. From the above table can be viewed texture and flavor of the cake A and B are different, while for the smell, taste, and colors have in common. So it can be concluded that between the two cakes A and B are same.